AN ORTHOTROPIC COSSERAT ELASTO-PLASTIC MODEL FOR LAYERED ROCKS - Adhikary D.P.; Guo H. (My University, 2002)
Modelling the behaviour of rock masses consisting of a large number of layers is often necessary in mining applications (e.g. coal mining). Such a modelling can be carried out in a discontinuum manner by explicit introduction of joints. When the number of rock layers is large, it is advantageous to devise a continuum-based model in which case the joints are considered to be virtually smeared across the mass. In this study, a fully elasto-plastic equivalent continuum model suitable for describing the behaviour of such layered rock masses is considered. The model is based on the Cosserat continuum theory and incorporates the moment stresses in its formulation. In contrast to the earlier Cosserat models, the possibility of rock layer plasticity is considered. The accuracy of the developed Cosserat model is verified against analytical and experimental results.